The constitution, administrative justice and social grants: unravelling the malaise in Eastern Cape Welfare Department - Maila, Malose Isaac (University of Limpopo (Turfloop Campus), 2007)
Refer to document
Thesis (LLM) --University of Limpopo, 2007
Keywords: Administration of Justice; Constitution of South Africa; 342.066068 MAI; South Africa -- Constitutional law; Administrative law -- South Africa